2018
DOI: 10.1038/s41598-018-32616-7
|View full text |Cite
|
Sign up to set email alerts
|

Humanin Prevents Age-Related Cognitive Decline in Mice and is Associated with Improved Cognitive Age in Humans

Abstract: Advanced age is associated with a decline in cognitive function, likely caused by a combination of modifiable and non-modifiable factors such as genetics and lifestyle choices. Mounting evidence suggests that humanin and other mitochondrial derived peptides play a role in several age-related conditions including neurodegenerative disease. Here we demonstrate that humanin administration has neuroprotective effects in vitro in human cell culture models and is sufficient to improve cognition in vivo in aged mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 57 publications
2
61
0
1
Order By: Relevance
“…Qin et al (2018) [9] have highlighted that exogenous HN treatment attenuated myocardial fibrosis and apoptosis in aged mice, suggesting a role for the mitochondria-derived peptide HN in cardioprotection. The study by Yen et al (2018) [10] addressed to HN a role in neuroprotection against cognitive aging in humans. In addition, Solanki et al (2018) [11] proposed a potential application of a HN derivative for treating age-related macular degeneration (AMD) since AGA-HNG may represent a promising therapeutic option for AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al (2018) [9] have highlighted that exogenous HN treatment attenuated myocardial fibrosis and apoptosis in aged mice, suggesting a role for the mitochondria-derived peptide HN in cardioprotection. The study by Yen et al (2018) [10] addressed to HN a role in neuroprotection against cognitive aging in humans. In addition, Solanki et al (2018) [11] proposed a potential application of a HN derivative for treating age-related macular degeneration (AMD) since AGA-HNG may represent a promising therapeutic option for AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Humanin, which was the first MDP discovered, was identified as a neuroprotective peptide using a screen searching for genes that could protect neuronal cells from amyloid-β toxicity (Hashimoto et al 2001 ; Hashimoto et al 2001a ; Hashimoto et al 2001b ; Yen et al 2018 ). It was later found to be an IGFBP-3 interacting protein and exerts its anti-apoptotic functions through direct binding to IGFBP-3 (Ikonen et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was later found to be an IGFBP-3 interacting protein and exerts its anti-apoptotic functions through direct binding to IGFBP-3 (Ikonen et al 2003 ). Over the past decade, the effects and mechanism of humanin action have been carefully characterized (Harada et al 2004 ; Kim et al 2016 ; Muzumdar et al 2009 ; Nashine et al 2017 ; Qin et al 2018 ; Yen et al 2018 ; Ying et al 2004 ). Humanin protects cells against various insults, such as oxidative damage and amyloid toxicity (Chai et al 2014 ; Klein et al 2013 ; Okada et al 2017 ; Paharkova et al 2015 ; Romeo et al 2017 ; Thummasorn et al 2016 ; Thummasorn et al 2017 ; Thummasorn et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Humanin, small humanin-like peptides (SHLPs), MOTS-c, and emerging new mitochondrial-derived peptides have highly specific and profound effects on various systems and organs. [28][29][30][31][32][33][34] Yen et al 27 reported that an mtSNP in the humanin smORF was associated with lower circulating levels of humanin and worse cognitive function. Moreover, the mitochondrialderived peptides SHLP2 and humanin protected against a model of macular degeneration in vitro.…”
Section: Discussionmentioning
confidence: 99%